The Influence of Organizational Culture on Employee Motivation and Discipline in the Education, Youth, and Sports Department of Karawang Regency - Rahmat Heryanto; Agus Cholik; Ahmad Kandias Bahaweres; Joean Himawan Fadlani Sam Aldia Plg; Nabiyil Anzal Diaswara (Lead Journal of Economy and Administration, 2024)
This study aims to analyze the influence of organizational culture on employee motivation and discipline in the Education, Youth, and Sports Department of Karawang Regency. Organizational culture is a crucial factor that can influence employee behavior and performance in government organizations. The study uses a quantitative approach with a survey method involving 65 employees as respondents. The research results show that organizational culture has a positive and significant influence on motivation (R² = 0.68) and employee discipline (R² = 0.72). These findings indicate the importance of strengthening organizational culture to improve motivation and discipline in the public sector.